Swift unveils the orbital period of IGR J18214-1318. Issue 2 (4th September 2020) - Cusumano, G; D'Aì, A; Segreto, A; La Parola, V; Del Santo, M
ABSTRACT: We analysed 13 yr of the Neil Gehrels Swift Observatory survey data collected on the high-mass X-ray binary IGR J18214-1318. Performing the timing analysis, we detected a periodic signal of 5.42 d. From the companion star characteristics, we derived an average orbital separation of $\sim 41 \rm R_{\odot }\simeq 2 R_{\star }$ . The spectral type of the companion star (O9) and the tight orbital separation suggest that IGR J18214-1318 is a wind-accreting source with eccentricity lower than 0.17. The intensity profile folded at the orbital period shows a deep minimum compatible with an eclipse of the source by the companion star. In addition, we report on the broad-band 0.6–100 keV spectrum using data from XMM–Newton, NuSTAR, and Swift, applying self-consistent physical models. We find that the spectrum is well fitted either by a pure thermal Comptonization component, or, assuming that the source is a neutron star accreting above the critical regime, by a combined thermal and bulk motion Comptonization model. In both cases, the presence of a local neutral absorption (possibly related to the thick wind of the companion star) is required.